End-to-end DSL architectures - Vermillion, Wayne C. (Cisco, 2003)
Implement DSL end-to-end solutions for all six current DSL architectures Coverage includes: All DSL varieties: U.S. and international varieties include ANSI and ITU standards as well as legacy and proprietary xDSL varieties, such as CAP Cisco DSL-related equipment that supports all the xDSL varieties and configurations in both Cisco IOS(r) Software and the graphical user interface Cisco DSL Manager (CDM) software All six architectures that implement DSL using TCP/IP, with in-depth discussion of the four most commonly-used architectures New standards and deregulation issues, including the ITU SHDSL standard and the evolving VDSL technology International regulatory and infrastructure issues, with measurements expressed for both U.S. and international audiences Common challenges and their solutions when deploying or migrating using xDSL, including voice-over-IP (VoIP) and multimedia traffic Using MPLS to move DSL-generated traffic through networks Bonus appendixes provide an overview of ATM as well as a tour of Cisco Long-Reach Ethernet (LRE) Virtual private networks, firewall security, e-commerce applications, multiple voice lines, and e-learning programs: Digital Subscriber Line (DSL) can bring all of these services to even the smallest network at an affordable price. End-to-End DSL Architectures shows how DSL can save you time and money and, most importantly, give you a competitive edge. Your primer and guide to all things DSL, this book is written for both U.S. and international audiences and builds on your basic knowledge of internetworking and TCP/IP to evaluate and compare all six TCP/IP architectures for DSL. In addition to addressing the fundamentals of DSL technology and offering guidance for planning future network evolution for a new or legacy DSL network, this book tells you what you really need to know, posing real-life challenges and explaining how to overcome common obstacles to implementation. To help you remember key concepts, each chapter of End-to-End DSL Architectures contains challenging, chapter-ending review questions that test your knowledge of the subject matter. A uniquely thorough glossary provides a concise yet full reference that is critical for sorting through the abbreviations and variations of DSL technology. Whether you are searching for a comprehensive reference to DSL standards and equipment or require an end-to-end solutions guide for xDSL architecture, End-to-End DSL Architectures is your complete solution fo ...